Challenges posed by COVID‐19 to people who inject drugs and lessons from other outbreaks. Issue 7 (22nd July 2020) - Vasylyeva, Tetyana I; Smyrnov, Pavlo; Strathdee, Steffanie; Friedman, Samuel R
Abstract: Introduction: In light of the COVID‐19 pandemic, considerable effort is going into identifying and protecting those at risk. Criminalization, stigmatization and the psychological, physical, behavioural and economic consequences of substance use make people who inject drugs (PWID) extremely vulnerable to many infectious diseases. While relationships between drug use and blood‐borne and sexually transmitted infections are well studied, less attention has been paid to other infectious disease outbreaks among PWID. Discussion: COVID‐19 is likely to disproportionally affect PWID due to a high prevalence of comorbidities that make the disease more severe, unsanitary and overcrowded living conditions, stigmatization, common incarceration, homelessness and difficulties in adhering to quarantine, social distancing or self‐isolation mandates. The COVID‐19 pandemic also jeopardizes essential for PWID services, such as needle exchange or substitution therapy programmes, which can be affected both in a short‐ and a long‐term perspective. Importantly, there is substantial evidence of other infectious disease outbreaks in PWID that were associated with factors that enable COVID‐19 transmission, such as poor hygiene, overcrowded living conditions and communal ways of using drugs. Conclusions: The COVID‐19 crisis might increase risks of homelessnes, overdoses and unsafe injecting and sexual practices for PWID. In order to address existing inequalities, consultations with PWID advocacy groups are vital when designing inclusive health response to the COVID‐19 pandemic.